USLE C factor determined by multi-temporal AVHRR/NOAA-14 data - Cavalli, Antonio Carlos; Garcia, Gilberto José [UNESP]; Zullo Jumor, Jurandir; Lombardi Neto, Francisco (My University, 2000)
This paper presents a methodology for the integration of AVHRR/NOAA-14 sensor data and USLE (Universal Soil Loss Equation) for identifying soil degradation and mapping erosion risks. The study area was the Piracicaba river watershed (5,457 km 2) located in São Paulo State, Brazil. Thirty percent of the region is covered with sugarcane plantations, which are the raw-material provider both for cane-sugar mills as for carburant-alcohol distilleries. To apply USLE equation, remote sensing and GIS techniques were used. The USLE C factor (use and management) indicates the soil protection provided by the vegetative cover and it changes gradually with the biomass yield. NDVI (Normalised Difference Vegetation Index) was selected to determine C factor since it is commonly used due its high sensitivity in monitoring green biomass. Channels 1 and 2 digital counts from seven AVHRR multi-temporal images from may/1996 to September/1997 were transformed from grey levels to percent of reflectance, since reflectance data are more suitable to get NDVI. Radiometric calibration was applied following the procedures of NOAA/NESDIS (National Environmental Satellite Data and Information Service). Through the NDVI data it was possible to characterise the sugarcane biomass growth and the values of predicting soil losses in a two-harvest period. Five classes of erosion risks were determined: (Class 1: 50.6% of sugarcane crop area; Class 2: 20.6%; Class 3: 24.3%; Class 4: 4.1%; Class 5: 0.3%). The correlation between erosion risk classes and soil types showed that sugarcane is mostly cultivated on soils with better physical characteristics, preferably on less steep slopes.
Keywords: Agriculture; Biomass; Erosion; Multi-temporal; Soil conservation